A ARTISTIC TRANSLATIONS WORKS OF ENGLISH WRITERS: The focus is on the role of literature in shaping national thinking. It is noted that in the literature in England - Sheyxmambetov, Server (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2022)
The article deals with the English literature. The focus is on the role of literature in shaping national thinking. It is noted that in the literature in England has had a significant influence on the formation of civilization. At the same time, English literature has historically performed an important educational role in the world.